How Does the ECHR Provide Protection in wartime? - Šmigová, Katarína (The ECHR at 70: The Central European Narrative, 2025)
The article aims to provide an overview of selected case-law of the European Court of Human Rights, covering the interplay between international humanitarian law and international human rights law from several points of view, especially in relation to the protection of the right to life and the right to liberty and security. Keywords: European Convention for the Protection of Human Rights and Fundamental Freedoms, armed conflicts, international humanitarian law, international human rights law